2023
DOI: 10.1080/15384047.2023.2237200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of USP29 as a key regulator of nucleotide biosynthesis in neuroblastoma through integrative analysis of multi-omics data

Abstract: Cancer cells show enhanced nucleotide biosynthesis, which is essential for their unlimited proliferation, but the underlying mechanisms are not entirely clear. Ubiquitin specific peptidase 29 (USP29) was reported to sustain neuroblastoma progression by promoting glycolysis and glutamine catabolism; however, its potential role in regulating nucleotide biosynthesis in tumor cells remains unknown. In this study, we depleted endogenous USP29 in MYCN -amplified neuroblastoma SK-N-BE2 cells by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(47 reference statements)
2
1
0
Order By: Relevance
“…13 Through integrative analysis of multiomics data, we recently identified USP29 as a key regulator of nucleotide biosynthesis in neuroblastoma cells, possibly by regulating MYC and E2F downstream pathways. 23 Consistent with our studies, USP29 was also reported to promote glycolysis by deubiquitinating and stabilizing HIF1α in hepatocellular carcinoma cells, thereby sustaining sorafenib resistance. 23 These findings suggest that USP29 plays a crucial role in regulating cancer cell metabolic reprogramming.…”
Section: Cancer Metabolismsupporting
confidence: 90%
See 1 more Smart Citation
“…13 Through integrative analysis of multiomics data, we recently identified USP29 as a key regulator of nucleotide biosynthesis in neuroblastoma cells, possibly by regulating MYC and E2F downstream pathways. 23 Consistent with our studies, USP29 was also reported to promote glycolysis by deubiquitinating and stabilizing HIF1α in hepatocellular carcinoma cells, thereby sustaining sorafenib resistance. 23 These findings suggest that USP29 plays a crucial role in regulating cancer cell metabolic reprogramming.…”
Section: Cancer Metabolismsupporting
confidence: 90%
“…23 Consistent with our studies, USP29 was also reported to promote glycolysis by deubiquitinating and stabilizing HIF1α in hepatocellular carcinoma cells, thereby sustaining sorafenib resistance. 23 These findings suggest that USP29 plays a crucial role in regulating cancer cell metabolic reprogramming.…”
Section: Cancer Metabolismsupporting
confidence: 90%
“…The study has shown that CRISPR-mediated depletion of ubiquitin-specific peptidase 29 (USP29) leads to the disruption of intermediates accountable for involvement in glycolysis and nucleotide biosynthesis in neuroblastoma cell lines ( Chandrasekaran et al, 2021 ). USP29 has also been shown to promote neuroblastoma progression by upregulating glycolysis and glutamine catabolism ( Kang et al, 2023 ). The study has also been conducted to target ferroptosis as an attractive strategy in cancer therapy ( Alborzinia et al, 2023 ).…”
Section: Applications Of Crispr/cas9 In Cancer Preclinical Studiesmentioning
confidence: 99%